Effectiveness of fascial manipulation on pain and disability in musculoskeletal conditions. A systematic review. (January 2021) - Arumugam, Karthik; Harikesavan, Karvannan
Abstract: Objective: To review the effectiveness of Stecco's fascial manipulation technique in patients with musculoskeletal pain. Design: Systematic review of interventional studies. Methods: A systematic search of literatures was performed in the electronic databases: PubMed, Cochrane, Scopus, ScienceDirect, and Ovid from January 2005 to December 2019. Studies were included if they were followed stecco's fascial manipulation as an intervention for the musculoskeletal conditions. RCTs and Non RCTs both were included in this review. Results: Thirteen studies met the eligibility criteria [RCTs-8, Pre-Post studies-3, Case reports-2]. Stecco's FM technique was followed in all the included studies. Five studies applied FM technique alone, while two studies added exercise along with FM and one study substitute session with manual therapy. Conclusion: This systematic review reported low to moderate quality evidence for the effect of FM in improving pain and disability in subjects with musculoskeletal pain conditions, when it is carried out as described in the Stecco's concept. Highlights: Fascia has a role in development of musculoskeletal pain. Addressing fascia will improve pain and disability. In clinical practice fascial manipulation can be used for treating painful musculoskeletal conditions. Future studies can address the fascia in various musculoskeletal conditions.